2017
DOI: 10.1590/0102-311x00099816
|View full text |Cite
|
Sign up to set email alerts
|

Antecedentes e elementos da vinculação do programa de alimentação escolar do Brasil com a agricultura familiar

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
23

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 10 publications
0
23
0
23
Order By: Relevance
“…In May 2018, the proposal for Provisional Measures to make feasible an agreement made with the cargo transport movement resulted in the cancellation of budget programs, which had already undergone previous cuts, such as agrarian reform and technical assistance, and rural extension programs [8], focused on preserving biodiversity, fighting gender violence, providing basic sanitation services, sustainable development, housing, as well as several programs of Health [13] and Education [60].…”
Section: Temer Era (May 2016-july 2018)mentioning
confidence: 99%
See 1 more Smart Citation
“…In May 2018, the proposal for Provisional Measures to make feasible an agreement made with the cargo transport movement resulted in the cancellation of budget programs, which had already undergone previous cuts, such as agrarian reform and technical assistance, and rural extension programs [8], focused on preserving biodiversity, fighting gender violence, providing basic sanitation services, sustainable development, housing, as well as several programs of Health [13] and Education [60].…”
Section: Temer Era (May 2016-july 2018)mentioning
confidence: 99%
“…In the last 15 years, several studies have been identified in the field of public policies on food and nutrition in Brazil, some of which have addressed the issue in a comprehensive way [4][5][6], while others have focused on the analysis of specific programs, such as the Programa Nacional de Alimentação Escolar (PNAE, National School Nutrition Program) [7][8][9][10]; the Programa Bolsa Família (PBF, Family Grant Program) [11][12][13][14]; the Programa de Aquisição de Alimentos (PAA, Food Acquisition Program) [15,16]; the government-backed economy restaurants program [17,18]; and the Sistema Nacional de Segurança Alimentar e Nutricional (SISAN, National System of Food and Nutrition Security) [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In order for the purchases and sales process to function properly, the various actors involved in this process have to be articulated. This is a fundamental factor previously mentioned by a number of authors (BACCARIN et al, 2017;SILVA;SOUSA, 2013;BRASIL, 2016a;SCHWARTZMAN et al, 2017;KILIAN, 2016). The articulation aims to identify the diversity and amount of food items available and that may be included in the menus which stresses the importance of dialogue and communication and the work as a team (BRASIL, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…Contudo, a estrutura não é condição necessária para ocorrerem os processos, ela cumpre suas finalidades se os processos forem adequados [14] . Dessa forma, Tanaka et al, baseado na tríade donabidianaestrutura, processo e resultado, propõe que a avaliação tenha inicialmente o processo como foco, por se constituir no componente essencial em que a interação com o usuário concretiza a ação de saúde [22] .…”
Section: Discussionunclassified